TARI NAMPYOG DALAM PIODALAN DI PURA SAMUANTIGA DESA ADAT BEDULU, KECAMATAN BLAHBATUH GIANYAR - I Gusti Ayu Made Widiantari (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
The sacred dance of Nampyog which is performed at the temple of Samuantiga, Bedulu, Blah- batuh, Gianyar has uniqueness among other dance in Bali 1) Nampyog dance is a dance used as a complement of the series of piodalan ceremony at Pura Samuantiga which means sanctification in the series of the Ida Bhatara will be going to have a process of embodyment (tedun) and neutral- izing the mrana (plague) 2) The dancers of the Nampyog dance are marely women who do not experience menstruation anymore (menopause). 3) The dancers of the Nampyog dance are people who commit themselves to dedicate their lifelong as the pengayah ‘non-payment workers’ called the permas. 4) If the permas are no longer capable of being the pengayah, they will be passed on by their heir (based on descendants) 5) The Nampyog dance is accompanied by several gamelan (gong, angklung) simultaneously by those people who also make ngayah on the piodalan ceremo- ny. 6) This sacred Nampyog dance is performed only on the piodalan ceremony at the temple of Samuantiga, Bedulu, Blahbatuh, Gianyar regency.